Tradisi Perang Obor di Tegalsambi Jepara: Kajian Maqasid Al-Shariah - Efa Ida Amaliyah (UIN Walisongo Semarang, 2019)
This paper examines about “perang obor” tradition seen from the perspective of the maqasid al-Sharia, especially maslahah al-mursalah. This needs to be studied, because Indonesia is a country that has many rituals or traditions in almost every region. On the other hand, there are some people who think that the rituals in each region are more inclined towards TBC (Taqlid Bid'ah Churafat). This research was conducted in Tegal Sambi Jepara with the ushul fiqh approach. Therefore, the study of maqasid al-Sharia, especially maslahah al mursalah is needed; it is because ritual be part of Indonesian society, especially Javanese society. The people of Tegal Sambi conduct a torch war ritual, meaning that the ritual brings their benefits, one of which is to give thanks to God and maintain friendship with neighbors.